PERANCANGAN SISTEM INFORMASI AKUNTANSI PENDAPATAN PADA PT. RITRA CARGO INDONESIA CABANG MAKASSAR - Arnida Arnida (AkMen JURNAL ILMIAH, 2012)
This Research aims to set up an Income Accounting Information system of PT. Ritra Cargo Indonesia Branch of Makassar, which is base on computer system. Data collection was taken from Income Accounting Information system of PT. Ritra Cargo Indonesia Branch of Makassar at from 09 July 2006 with field research method and also using documentation, observation and interview system. The obtained data then analized by using DFD System Design (Data Flow Diagram), HIPO (Hierarchy Plus Input-Process-Output) and Data Dictionary. The result of analysis show that selling data the process in simple so that often him happened mistake in data processing and delay of transaction process. Therefore by this design, it can lessen mistake in presentation of monetary data, quicker and also in the presentation of and data can be presented appropriately, faster, accurately and safely.